Genome sequencing and phylogenetic analysis of SARS-CoV-2 isolated from patients with COVID-19 in Hospital Canselor Tuanku Muhriz (HCTM), Malaysia - Kon, Ken Wong; Noor Zetti Zainol Rashid,; Umi Kalsom Ali,; Nur Hazlin Chong,; Shairah Abdul Razak,; Najma Kori,; Petrick Periyasamy,; Alfizah Hanafiah, (Penerbit Universiti Kebangsaan Malaysia, 2024)
SARS-CoV-2 infection has reached pandemic status in numerous countries worldwide, including Malaysia. Monitoring the genetic diversity of SARS-CoV-2 is essential for identifying the emergence and prevalence of novel variants in different geographical areas. From May to October 2021, this research endeavor analyzed the SARS-CoV-2 genome of 40 COVID-19 patients diagnosed using real-time RT-PCR at the local hospital HCTM-UKM. The process involved extracting RNA from these patients, which was subsequently subjected to whole genome sequencing. Our discovery underscores the primary strains responsible for the fourth wave of the COVID-19 pandemic in Malaysia in May 2021 were the Beta variant, primarily associated with the B.1.351 lineage. However, by October 2021, the Delta variant had become predominant and was categorized within the AV.59 and AV.79 lineages. Genomic epidemiological analysis showed about 19 amino acid mutations in the spike protein that were prevalent during the Beta variant outbreak. Among these, the N501Y mutation is particularly noteworthy as it significantly enhances the virus’s ability to bind to the ACE2 receptor. Additionally, 32 amino acid mutations were identified during the Delta variant outbreak, with the T478K mutation being linked to increased viral infectivity and affecting the virus’s affinity for human cells. Throughout our research, we consistently noted the presence of Spike D614G mutations in all the strains we collected which is known to reduce S1 shedding and increase infectivity. These findings could contribute significantly to our understanding of specific variants due to their clinical implications and rapid spread within the community.